Baogutu: An example of reduced porphyry Cu deposit in western Junggar - Cao, M.; Qin, K.; Li, G.; Jin, L.; Evans, Noreen; Yang, X. (Elsevier Science BV, 2014)
Classic oxidized porphyry copper deposits (OPCD) are characterized by high tonnage and elevated fO2 and contain highly oxidized minerals including primary anhydrite and hematite. In contrast, the Baogutu deposit contains abundant hypogene pyrrhotite and methane-rich fluid inclusions, characteristic of lower tonnage, reduced porphyry copper deposits (RPCD). Mineral paragenesis and mineral chemistry studies reveal two mineralization periods (magmatic and hydrothermal) with the hydrothermal period further subdivided into three paragenetic stages including Ca–Na alteration, potassic alteration and propylitization, locally overlapped by phyllic alteration.Several independent geothermometers indicate that the temperatures of the magma, potassic and propylitization alteration are estimated to be 600–900 °C, 200–400 °C and 200–300 °C, respectively. Multiple indicators including mineral assemblages, apatite SO3 content, whole rock Fe2O3/FeO ratios and fluid compositions indicate the fO2 of the magma and hydrothermal fluid to be NNO and NNO–NNO-2, respectively. Hydrothermal fluids associated with primary biotite yield log(fH2O/fHCl)fluids values of 4.8–6.2 for diorite and 4.1–4.5 for granodiorite porphyry. The logfS2 of the magmatic and potassic alteration are estimated to be 0.7 to 3.0 and 5.5 to 11.0, respectively, based on pyrrhotite and sulfide assemblages. Mineral assemblage and hessite composition suggest the logfTe2 of the potassic alteration is 8.5 to 14.5.The low tonnage Baogutu deposit displays significantly lower fO2 than OPCDs (> NNO + 2), and, on this basis, could be classified as a RPCD. Other physicochemical conditions including T, fS2, log(fH2O/fHCl)fluid do not show obvious differences to those of OPCDs. We deduce that the low fO2 of Baogutu metallogenic granitoids and aqueous fluids likely produced the unusual pyrrhotite–arsenopyrite mineral assemblage, and the NaCl–H2O–CH4–CO2 ore-forming fluids and small tonnage typical of RPCDs. Previous obtained fluid inclusion H–O isotope data and sulfide S–Pb isotope data suggest the methane-rich ore-forming fluids were derived from deep mantle source with little contamination from sedimentary components. However, detailed studies are needed to clarify the origin of the CH4.